Assessing the risk to the conservation status of temperate rainforest from exposure to mining, commercial logging, and climate change: A Tasmanian case study. (November 2017) - Mackey, Brendan; Cadman, Sean; Rogers, Nicole; Hugh, Sonia
Abstract: Formal protected areas are a critical conservation measure so long as their tenure is defined and secure and they are well managed. Protected areas in developed countries are assumed to meet these criteria and therefore have not attracted the level of attention given to the adequacy of protected areas in developing countries. We investigate this assumption using as a case study the southern temperate rainforests of Tasmania, Australia. We examine the extent to which these rainforests are protected from potential exposure to mining, commercial logging and climate change. We analyse the tenure of Tasmania's rainforests and identify the protected area categories that prohibit or allow mining or logging. We also model the potential distribution of Nothofagus cunninghamii, a dominant rainforest canopy tree species, to future climate and compare this with modelled current and future forest fire danger index. Results showed that 90% of the total area of Tasmanian rainforest (715, 773 ha − 1 ) is in a reserve. However, the area of rainforest in reserves secured from mining and/or commercial logging is only 47% (335, 863 ha − 1 ) as 43% (308, 897 ha − 1 ) is in a reserve category where these land uses are permitted. The protected area category with the highest level of protection, prohibiting all mining and logging, is the Tasmanian Wilderness World Heritage Area which encompasses 325, 920 ha − 1 of temperate rainforest. During a recent legislative review, 66, 012 ha − 1 of rainforest in protected areas was downgraded to a reserve category that permits logging or mining. A key conservation instrument therefore is the Management Plan for the World Heritage Area as it overrides land use activities otherwise permitted including the 21, 257 ha − 1 which is on a State-defined land tenure that allows for logging or mining. Climate change impacts, as modelled, suggest the main conservation challenges are in maintaining the integrity of the remaining intact rainforest blocks and better managing ignitions from lightning strikes and arsonists in the coniferous and alpine rainforests. Allowing structural degradation and fragmentation to intact rainforest blocks will reduce their capacity to buffer meso-climatic variability and resist fire events thereby undermining their ecosystem integrity. Noting that Aichi Target 11 includes the requirement that reserves are effectively managed, our case study highlights that assessing the effectiveness of a reserve system is not necessarily a straightforward matter as governance systems and regulatory frameworks involve a mix of international obligations, national and subnational policies and statutes, along with other agreements, administrative arrangements and plans of management, which can provide for a range of land use activities and be subject to modification over time.